Chitosan Microparticles Coupled with MAGE-AX and CpGs as a Treatment for Murine Melanoma - Gabriela Piñón-Zárate; Beatriz Hernández-Téllez; Ariel Ramírez-Cortés; Katia Jarquín-Yáñez; Enrique A. Sampedro-Carrillo; Miguel A. Herrera-Enríquez; Christian A. Cárdenas-Monroy; Andrés E. Castell-Rodríguez (Pharmaceutics, 2025)
Background/Objectives: One current cancer treatment is immunotherapy, in which tumor antigens (such as MAGE) or adjuvants (such as CpGs) can be used to induce the destruction of tumor cells by the immune system; however, the therapeutic response is generally weak. Therefore, it is necessary to develop a strategy that increases the immune response induced by tumor antigens and CpGs. We propose the coupling of tumor antigens and adjuvants to chitosan (Cs) microparticles to improve the immune response against cancer, as these microparticles can activate the innate immune response when recognized by macrophages and dendritic cells (DCs). Methods: Cs microparticles coupled with CpGs and tumor antigens were constructed with the emulsification method; then, their morphology, in vitro biological effect on DCs, and therapeutic effect in a murine melanoma model were analyzed. Results: The Cs microparticles showed a rounded morphology and a size of approximately 5 μ; in addition, they were not cytotoxic in in vitro assays and induced the production of IFNα. Finally, in the murine model of melanoma, treatment with Cs microparticles coupled to MAGE or CpGs reduced the tumor growth rate and increased both survival and the presence of cell death areas in the tumor parenchyma in contrast to the control group. Conclusions: The results suggest that treatment with Cs microparticles coupled to tumor antigen and/or CpGs can be considered a promising strategy in the field of immunotherapy based on the use of biomaterials.